The Visionary Leadership of Pesantren: Adaptive Strategies in Response to the Pesantren Law - Utomo, Budi; Farra Nadia (Islamic Educational Management Programme, 2024)
Leadership is the art of inspiring others to achieve organizational goals. In the context of pesantren , visionary leadership is needed to ensure that institutions remain competitive and sustainable. This study aims to analyze the response of Islamic boarding schools to the Islamic Boarding School Law from a leadership perspective. This qualitative-descriptive study was conducted at the Darul Amin Islamic Boarding School. Data were collected through interviews with three informants, then critically examined to identify innovative practices, particularly the application of visionary leadership. The Islamic Boarding School Law emphasizes improving service quality—a desirable goal achieved through adaptive visionary leadership. The results show a dominant visionary leadership style, reflected in the boarding school's policies and strategic initiatives. The main policy implemented is the digitization of the pesantren system. Its implementation includes: integration of a digital-based curriculum; improvement of administrative services through applications; digital management of pesantren business units; and strengthening of community relations for regular coverage of pesantren activities. These findings confirm that leadership renewal—particularly vision-oriented and adaptive leadership—is a key factor for the sustainability of Islamic pesantren.